The Impact of Teacher Leadership on Teacher’s Performance and Students’ Development for School Improvement: a case study of Dubai Private Kindergarten - ALSHIZAWI, FATIMA ALI (2023)
Teachers' leadership is essential to school success, since with an effective leadership style, a teacher will develop and perform well in both teaching and learning and as a result, students' achievement will automatically increase. This study examines the impact of teacher leadership practices on the performance and achievement of teachers and students. A case study was conducted using a mixed data collection approach. The first step was to complete a self-administered questionnaire among teachers in a Dubai private kindergarten. A non-probability sampling technique was then used to conduct semi-structured interviews with two head coordinators and two lead teachers. The study was guided by the following questions: to what extent do teachers practice teacher leadership, what characteristics or factors are involved in an effective teacher leadership style, how they influence school performance and evaluation, and what role teacher leadership plays in the overall performance of teachers and students, the collective performance of schools, and school management. The analysis of data showed that there is a positive relationship between effective lead teachers and the improvement of the teaching and learning process. This includes both teachers' performance and students' outcomes. The results of the quantitative analysis of the study indicated that teachers are often involved in certain leadership roles, as measured by questionnaire items. In contrast, other activities such as leading action research or participating in professional groups, are practiced infrequently. Data from interviews revealed that teachers perceive that school administrators generally encourage them to take on leadership roles. However, administrators also heavily depend on group-based teachers to lead. In addition, school contextual factors, such as lack of time, resource shortages, overload of work, and leadership style, as well as teachers' assumptions about and willingness to assume additional leadership responsibilities, are obstacles to maximizing the potential for teacher leadership in this kindergarten. This study added and narrowed the current research on teacher leadership's impact on both teachers' and students' development in the UAE to a private kindergarten in Dubai. It should be noted that the findings of this study cannot be generalized and are only applicable to certain contexts, which constitutes a limitation of the study. For this purpose, It is suggested that teacher leadership should be promoted on a broader scale in UAE schools. Further research can focus on what teacher leadership practices are most appropriate and how school leaders can deal with crises for school improvement.